When it comes to leadership, does gender matter? - Othman, Anwar Hasan Abdullah (Arabian Group of Journals, 2012)
Purpose – Whether men and women behave differently in leadership roles is a much-debated issue. Although there is consensus that woman, face more barriers to becoming leaders than men specifically in conservative societies and some developing countries. Therefore, this paper aims to investigate the differences between male and female leadership styles.